2017
DOI: 10.1002/brb3.731
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐enhanced magnetic resonance imaging combined with electrophysiology in the evaluation of visual pathway in experimental rat models with monocular blindness

Abstract: PurposeOur study aimed to explore the feasibility of manganese‐enhanced magnetic resonance imaging (MEMRI) combined with visual evoked potentials (VEP) and auditory evoked visual cortex responses (AVR) in evaluating for the establishment of visual/auditory compensatory pathways after monocular blindness.Materials and MethodsA total of 14 healthy neonatal male Sprague‐Dawley rats were randomly divided into two groups (n = 7 for Groups A and B). Right optic nerve (ON) transection was performed on the 7 rats of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…With an increase in detectable projections from both the retina and visual cortex following enucleation, this study demonstrates the ability of MEMRI to not only map the visual system, but also to detect finer neuroplastic changes. Other studies have since demonstrated the ability of MEMRI to detect sensory system-wide neuroplastic changes (Tang et al, 2017a,b).…”
Section: Memri In Cns Imagingmentioning
confidence: 99%
“…With an increase in detectable projections from both the retina and visual cortex following enucleation, this study demonstrates the ability of MEMRI to not only map the visual system, but also to detect finer neuroplastic changes. Other studies have since demonstrated the ability of MEMRI to detect sensory system-wide neuroplastic changes (Tang et al, 2017a,b).…”
Section: Memri In Cns Imagingmentioning
confidence: 99%